2018
DOI: 10.1002/hep.29519
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cancer cell stemness by depletion of macrohistone H2A1 in hepatocellular carcinoma

Abstract: The absence of histone variant macroH2A1 confers a CSC-like phenotype to HCC cells in vitro and in vivo that depends on Ser536 phosphorylation of nuclear factor kappa B p65; this pathway may hold valuable targets for the development of CSC-focused treatments for HCC. (Hepatology 2017).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 39 publications
5
77
1
Order By: Relevance
“…Most research efforts have focused on DNA methylation and posttranslational modification of canonical histones H2A, H2B, H3, and H4. We recently investigated the loss of the histone variant macroH2A1a as a mechanism that increases CSClike properties of hepatic cancer cells [7]. MacroH2A1 is an histone variant of the H2A histone family that contains a histone-fold domain with 66% identity to replication-coupled histone H2A, and a C-terminal linker that connects the histone fold domain to a macro domain [8].…”
Section: Introductionmentioning
confidence: 99%
“…Most research efforts have focused on DNA methylation and posttranslational modification of canonical histones H2A, H2B, H3, and H4. We recently investigated the loss of the histone variant macroH2A1a as a mechanism that increases CSClike properties of hepatic cancer cells [7]. MacroH2A1 is an histone variant of the H2A histone family that contains a histone-fold domain with 66% identity to replication-coupled histone H2A, and a C-terminal linker that connects the histone fold domain to a macro domain [8].…”
Section: Introductionmentioning
confidence: 99%
“…An increased number of senescent cells are associated not only to chemotherapeutic treatment but also to age‐related tissue degeneration towards HCC . In mice, impaired immune surveillance of senescent hepatocytes induces HCC, indicating that senescence surveillance is important for tumour suppression in the liver .…”
Section: Discussionmentioning
confidence: 99%
“…This concentration is only slightly cytotoxic to HCC cells, inducing senescence in ~40% of cells. 9,15,19 We then washed out the DXR and incubated the cells in normal medium for a further 5 days. Upon trypsin-mediated cell detachment,…”
Section: Iodixanol Density Gradient-based Centrifugation Separates mentioning
confidence: 99%
“…Recent studies have reported the inactivation of somatic mutations in gene-encoding BRCA-1-associated protein 1 (BAP1) in about 84% of metastasizing UMs [14]: the high frequency of BAP1 mutations in metastatic UMs encouraged us to search for new therapeutic strategies with the target molecule BAP1, which have deubiquitinase activity on histone H2A [15,16]. In different tumors, including skin melanoma, mH2A and its variants, which are widely distributed along chromatin [17][18][19], have been regarded as a potential prognostic marker [20,21].…”
Section: Discussionmentioning
confidence: 99%